Early biodistribution and persistence of a protective live attenuated SIV vaccine elicits localised innate responses in multiple lymphoid tissues. - Deborah Ferguson; Giada Mattiuzzo; Claire Ham; Richard Stebbings; Bo Li; Nicola J Rose; Edward T Mee; Deborah Smith; Mark Page; Martin P Cranage; Neil Almond; Greg J Towers; et al. (PLoS ONE, 2014)
Vaccination of Mauritian cynomolgus macaques with the attenuated nef-truncated C8 variant of SIVmac251/32H (SIVmacC8) induces early, potent protection against pathogenic, heterologous challenge before the maturation of cognate immunity. To identify processes that contribute to early protection in this model the pathogenesis, anatomical distribution and viral vaccine kinetics were determined in relation to localised innate responses triggered by vaccination. The early biodistribution of SIVmacC8 was defined by rapid, widespread dissemination amongst multiple lymphoid tissues, detectable after 3 days. Cell-associated viral RNA dynamics identified mesenteric lymph nodes (MLN) and spleen, as well as the gut mucosae, as early major contributors of systemic virus burden. Rapid, localised infection was populated by discrete foci of persisting virus-infected cells. Localised productive infection triggered a broad innate response, with type-1 interferon sensitive IRF-7, STAT-1, TRIM5α and ApoBEC3G genes all upregulated during the acute phase but induction did not prevent viral persistence. Profound changes in vaccine-induced cell-surface markers of immune activation were detected on macrophages, B-cells and dendritic cells (DC-SIGN, S-100, CD40, CD11c, CD123 and CD86). Notably, high DC-SIGN and S100 staining for follicular and interdigitating DCs respectively, in MLN and spleen were detected by 3 days, persisting 20 weeks post-vaccination. Although not formally evaluated, the early biodistribution of SIVmacC8 simultaneously targets multiple lymphoid tissues to induce strong innate immune responses coincident at the same sites critical for early protection from wild-type viruses. HIV vaccines which stimulate appropriate innate, as well as adaptive responses, akin to those generated by live attenuated SIV vaccines, may prove the most efficacious.